2003
DOI: 10.1046/j.1364-3703.2003.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Potato leafroll virus: a classic pathogen shows some new tricks

Abstract: SUMMARY Taxonomy: PLRV is the type species of the genus Polerovirus, in the family Luteoviridae. Isolates are known from most continents, presumably all spread in potato material derived from the Andean region of South America.  Physical properties: PLRV particles are isometric and c. 25 nm in diameter. They contain one major (c. 23 kDa) and one minor (c. 80 kDa) protein. The genome is a single 5.8 kb positive sense RNA that has neither a 5′‐cap nor 3′ poly(A) but carries a VPg.  Host range: PLRV has a limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 56 publications
(75 reference statements)
1
57
0
3
Order By: Relevance
“…The prevailing hypotheses to explain the phloem limitation of poleroviruses such as PLRV are that the virus is unable to suppress plant defense mechanisms outside of the phloem or that the viruses lack a movement protein that can function in nonvascular tissues (36). Our current study has demonstrated an alternative explanation: the virus encodes a protein, P5, which confines the virus to phloem tissues.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The prevailing hypotheses to explain the phloem limitation of poleroviruses such as PLRV are that the virus is unable to suppress plant defense mechanisms outside of the phloem or that the viruses lack a movement protein that can function in nonvascular tissues (36). Our current study has demonstrated an alternative explanation: the virus encodes a protein, P5, which confines the virus to phloem tissues.…”
Section: Discussionmentioning
confidence: 68%
“…Although luteovirids encode at least two movement proteins and move locally and long distance in vascular tissues, they are unable to move between nonvascular cells or between nonvascular and vascular tissues (36). This phloem limitation is generally attributed to a lack of or an inability of luteovirid movement proteins to function in nonvascular tissues or because the virus cannot suppress a silencing-based plant defense mechanism outside of phloem tissues (5,36).…”
mentioning
confidence: 99%
“…The PLRV forms icosahedral particles containing a 5.8 kb single-stranded (+) sense RNA that consists of eight open reading frames (ORFs) (Harrison, 1984;Taliansky et al, 2003). As PLRV is a member of the genus Polerovirus (family Luteoviridae), unlike the majority of plant viruses PLRV is restricted to the phloem-associated tissues (Gray and Gildow, 2003;Nurkiyanova et al, 2000;Taliansky et al, 2003). It is transmitted by a limited number of aphid species in a non-propagative circulative manner from plant to plant (Gray and Gildow, 2003;Harrison, 1985;Taliansky et al, 2003).…”
mentioning
confidence: 99%
“…6 to 8). Alternatively, these data may represent interactions with virions at different stages of assembly that copurified with intact virions (59,68) or even multimeric forms of the structural proteins (58) that could act in trans to regulate PLRV infection. It is known that viral proteins can be a part of many different host protein complexes that are dynamically regulated throughout the course of an infection (73,74).…”
Section: Discussionmentioning
confidence: 99%
“…Only one model ( Fig. 8C and D) predicted the N-terminal sequence of a CP monomer to be surface exposed, a model that is supported by epitope mapping (59) and hypothesized to occur during virus disassembly (68). Visualization of the PsbQ2-CP dimer interface using this CP dimer model predicts two general interaction topologies, one where PsbQ2 interacts with the internal CP arginine-rich domain (Fig.…”
Section: Complete Loss Of Systemic Infection Is Indicated By a Minus mentioning
confidence: 99%